OCH Ameliorates Bone Marrow Failure in Mice via Downregulation of T-Bet Expression - Xiaohong Qiao; Xiaotian Xie; Wei Shi; Jinqing Tang; Yuexia Shao; Fuxing Li (Journal of Immunology Research)
The aim of this study is to evaluate the immune mechanism of OCH in the treatment of AA (also named bone marrow failure, BMF) induced in mice. OCH at a dose of 400 μg/kg was injected intraperitoneally (I.P.) prior to the induction of BMF. Our study showed that the incidence of BMF was 100% in BMF group and 13% in OCH treatment group. Significant higher level of IL-4 and lower level of IFN-γ were observed in OCH group than that in BMF group (P<0.05) as well as untreated group over BMF (P<0.05). However, there was no significant difference between OCH and untreated group. Compared with untreated, the expression level of T-bet in OCH and BMF was all significantly higher. However, T-bet expression level was lower in OCH than in BMF. In addition, OCH treatment increased NKT cell fractions of bone marrow and the colonies of CFU-GM. In conclusion, treatment of OCH prior to the induction of BMF could prevent the incidence of BMF possibly through downregulating T-bet expression leading to the transition of immune response from Th1 to Th2, suggesting OCH might be a new therapeutic approach in the treatment of BMF or AA.